Implications for using Shipping Containers to Provide Affordable Housing - Maphumulo, Minenhle (University of the Witwatersrand; Faculty of Engineering and the Built Environment, 2016)
Southern African cities are more and more characterised by rapid urbanisation. Urban planners and other spatial practitioners are thus increasingly expected to develop innovative strategies around affordable housing to accommodate the influx populations moving to urban environments in the 21st century. In light of this, understanding the underlying elements that influence the perceptions towards alternative building materials is critical to identifying the implications of employing such components for housing. As such, shipping containers are gradually becoming a part of many contemporary cities around the world; however, that is still not the case in South African cities – even though, they are widely available and according to trends, they are a low-cost building resource. To interrogate this, the 61 Countesses container residential building in Windsor East, Johannesburg has been selected for this case study to reveal residents’ opinion. Public attitudes play a significant role in the success or failure of planning initiatives (Tighe, 2010). Recognising and understanding the aspects that sway public acceptance and the opposition is an important step in the planning process, this is especially the case for affordable housing developments, as they are often confronted by many barriers. This research report provides the residents’ perceptions of shipping container housing developments, based on their experience, with the purpose of, first, understanding the views held towards shipping containers as building units, and second to review the contribution that this particular building has made toward densifying the Windsor East neighbourhood. This research report further offers a cross-examination of neighbours’ opinions of shipping container housing and social housing to reveal a link between the two. This is to build a better understanding of the possibilities of shipping container affordable housing in the Johannesburg context. This research report shows how shipping containers have been used and received in Windsor East. This research also indicates that shipping containers are more accepted in rental housing typologies. The results and recommendations offer urban planners, policy makers and developers insight of shipping container residential opinion, thereby informing them of the possibilities for shipping containers in the South African context.
Planning Honours Report 2016, Wits University